Maternal and Perinatal Outcome in Women with Gestational Diabetes Mellitus - Sabina Yeasmin, Most; Tahmina Sultana, Begum; Anjum Nourin, Nishat; Nurul Haque, Md; Jalal Uddin, M (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2025)
Back ground: Gestational Diabetes Mellitus (GDM) is a growing global Public health problem, with a rising prevalence and is associated with short and long-term health consequences for the mother and baby. Objective of this study is to assess the maternal and perinatal outcome of pregnancy with GDM. Materials and methods: This prospective observational study was conducted at Chattagram Maa-O-Shishu Hospital Medical College from January to December 2021 on all admitted pregnant women with Gestational Diabetes Mellitus (GDM) more than 28 weeks. Detailed history, clinical examination, associated conditions, mode of delivery,fetal conditions and investigation were analyzed. Results: A total of 218 GDM Cases were reported amongst 5724 pregnant women with its incidence of 3.8%. GDM was seen commonly in patients (38.07%) with age group between 26-30 years, multigravida (74.8%), over weight (58.72%), positive family history (62.4%) and past poor obstetric history (51%). There were no maternal mortality. However, pregnancy complications were remarkably higher, the most common maternal complications were vaginal candidiasis (69.7%), urinarytract infection (46.8%), polyhydramnios (42.7%), pre-eclampsia (40.8%), PROM (28.4%), preterm- labor (22%). The commonest mode of delivery was caesarean section (65.1%). Common perinatal complications were prematurity (25.2%), hypoglycemia (15.5%), perinatal asphyxia (9.9%), stillbirth (6.4%), macrosomia (11.6%) and most common causes of neonatal death were prematurity and neonatal sepsis. Conclusions: Gestational Diabetes mellitus is associated with significant maternal and perinatal morbidity as well as perinatal mortality. Hence early detection and treatment would reduce the feto-maternal morbidity and mortality Chatt Maa Shi Hosp Med Coll J; Vol.23 (1); January 2024; Page 68-72